Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen di Toko Family Cukir Diwek Jombang - Ulfi Rahmawati (BIMA : Journal of Business and Innovation Management, 2020)
The purpose of this research to know the effect of quality’s service that consist tangible, reliability, responsiveness, assurance and empathy in partial to gather the effect of consumer satisfaction in the Family Cukir Diwek Jombang Shop. This research is quantitative research that used sample in purposive sampling technique with the total of sample around 133 consument in the Family Cukir Diwek Jombang Shop. Data collection techniques using interview observation, interview and questionnaires. Data analysis techniques using linier regression. Research shows, based on analysis of the determin-effecient analysis coefficient Determination drawn from the R square (coefficient determination) a total 0.740 means that 70,4% of customer satisfaction is affected by a quality service variable made up of tangible, reliability, responsiveness, assurance and empathy whereas are effected by other variable not discussed in this study. There is a partial significant effect on variablereliability, responsiveness, assurance, and empathy to consumers’ satisfaction with significant result t (0,000) < α 0,005.